PROJECT TECHNOLOGY AS A MEANS OF DEVELOPING THE INDIVIDUALITY OF CADETS - Наркулова, Индира (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2024)
The article is devoted to the use of the project method in Russian language classes and its role as a means of developing students' motivation and improving the quality of the educational process.